Electricity market price analysis using time series clustering - Martins, A. A. A. F.; Lagarto, J.; Cardoso, M. G. M. S. (16th International Conference on the European Energy Market (EEM), 2019)
The creation of the internal market of electricity has long been a goal of the European Union, for which it has established common rules through the directive 2009/72/EC. In this context, the analysis of electricity markets operation of the different countries that will form the internal market is of the utmost importance. In this work, we use clustering techniques to analyze 26 time series of day-ahead electricity prices from European markets between 2015 and 2018 in order to identify different price patterns. The cluster technique proposed uses a combination of three dissimilarity measures for time series: Euclidean, Pearson correlation based and periodogram based. Results show that there is a clear distinction between Northern markets, especially Nord Pool, and Southern markets, MIBEL and Italy. Moreover, results also show that despite some market prices presenting similar behaviors, a full integrated European electricity market is yet to be accomplished.